PELESTARIAN KEDAULATAN NEGARA MELALUI ARBIRASE HUKUM INTERNASIONAL - Ni Wayan Restiti; Dewa Gede Sudika Mangku; Muhamad Jodi Setianto (Universitas Pendidikan Ganesha, 2022)
This article was created to understand that the concept of state sovereignty is very interesting and inspiring in dynamic discourse in the fields of law and politics. The research method used in this case is a literature study method. The results of this study indicate that state sovereignty in the economic field and international arbitration investment as a dispute resolution.